Study of Competitiveness In Bread Janur Smes In Mandonga District, Kendari City: The Method Interpretive Structural Modeling - Darno Darno; Sarinah Sarinah; Muhammad Syukri (Jurusan Ilmu dan Teknologi Pangan, Fakultas Pertanian,, 2022)
This study aims to determine what factors are needed for the competitiveness of Roti Janur SMEs in Mandonga District, Kendari City. Factors needed for the competitiveness of janur bread SMEs in Mondonga sub-district, Kendari city, namely product excellence, innovation, and human resources using the ISM method to identify problems in janur bread SMEs. Interpretive Structural Modeling (ISM) is a systematic application of elementary graph theory in such a way that its theoretical, conceptual, and computational advantages are utilized to explain conceptual relationships between elements. The program objectives consist of product uniqueness (1), product quality (2), product price (3), product standardization (4), and program needs, namely product packaging (1), renewable tools (2), raw materials (3), strategy (4), and planning for innovation (5) and required activities/changes such as selecting a competent workforce (1),. Selection of workers who have skills in their respective fields (2), SME training (3), quality aspects (4), and educational background (5). From the results of the ISM software, it was found that the critical factor that drives the competitiveness of janur bread SMEs in Kendari City, Mondonga District, is the product standardization factor.